Enhancing Language Proficiency in Vocational High School Students through Experiential Learning-Based Movie at SMK YAPIM Riau - Safriyani Novitri; Yulianto; Johari Afrizal (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
This qualitative research explores various effective steps to enhance students’ language proficiency through the experiential learning approach. Discussions and reflections are identified as factors that can directly promote students’ understanding in line with the principles of experiential learning. The use of movie-based learning utilizing gadgets and social media is also a major highlight. The research emphasizes the importance of critical thinking in enhancing language skills based on movie. Feedback and support from teachers are considered key factors in improving students’ literacy. The research results indicate that out of the 20 students involved, 16 experienced a significant improvement in learning outcomes, while the remaining 4 students were already able to engage in experiential learning.